Roundtable: the Latin American state, Pink Tide, and future challenges. Issue 1 (2nd January 2023) - Larrabure, Manuel; Levy, Charmain; Cameron, Maxwell A.; Foweraker, Joe; Lavinas, Lena; Spronk, Susan Jane
ABSTRACT: In May 2020, the guest editors of this special number organized a roundtable discussion centred on six themes and covered a broad range of topics pertaining to Latin American development, politics and economics. The context of 'pink tides' and 'right turns' are a backdrop that represent both the consequences and the lead up to what comes next. At the centre of the analysis are the core dynamics of the political systems we intend to explore. The perspectives of the roundtable represent a theoretical and methodological spectrum ranging from neoWeberianinstitutionalism closely associated with the work of O'Donnell, and comparative studies of democratization, to critical-world systems analysis, associated with Marxian historical materialism, typically found within the development studies and political economy disciplines. Although the authors may draw more from one end of the spectrum than from the other, throughout their research careers, they have considered all of them in their intellectual reflections.